Effect of empowerment: how and when do high-involvement work practices influence elder employees’ innovative performance? - Jiang, Daokui; Zhang, Yiting; Zhu, Honghong; Wang, Xiaoyu (Frontiers in Psychology, 2024)
Introduction In today’s fast-paced business environment, innovation from elder employees is increasingly vital to organizations. High-involvement work practices that emphasize engagement and empowerment have a significant impact on the innovation performance of these employees, harnessing their wealth of experience and fostering organizational growth. However, most of the current research on innovation performance focuses on the single factor of the individual or the organization, and most of them focus on the linear relationship; research on the factor of human resource practices, in particular high-involvement work practices, is inadequate. Methods Based on social exchange theory, this paper uses structural equation modeling (SEM) to examine the impact of high-involvement work practices on elder workers’ innovation performance using 278 valid samples from three time points, and the non-linear effects of exploratory and exploitative innovation on elder workers’ innovation performance. Results (1) There is no significant relationship between high-involvement work practices and elder employees’ innovation performance. (2) Exploratory innovation has a significant U-shaped relationship with innovation performance, i.e., as the level of exploratory innovation increases, the innovation performance of elder employees first decreases and then increases. There is a significant inverted U-shaped relationship between exploitative innovation and innovation performance, i.e., as the level of exploitative innovation increases, innovation performance first increases and then decreases. High-involvement work practices have a U-shaped effect on elder employees’ innovation performance through exploitative innovation. (3) Transformational leadership moderates the direct effects of high-involvement on exploratory innovation and elder employees’ innovation performance, and transformational leadership moderates the U-shaped effect of high-involvement work practices on elder employees’ innovation performance through exploratory innovation. Discussion The conclusion is helpful for organizations to enhance elder employees’ innovation performance by enriching high-involvement work practices.